Optimizing EFL Learners’ Outcomes in Formative Assessment through Educational Technology Integration - Chraa, Ayad; Alidrissi, Mohamed (International Journal of Language and Literary Studies, 2025)
The introduction of technology in language teaching has significantly transformed assessment practices, particularly in the domain of formative assessment. This study examines the impact of technology-based assessment tools on the performance of English as a Foreign Language (EFL) learners. Situating its foundation in Kane’s system of argumentative validity, the research explores how technology can enhance formative assessment by providing immediate feedback, individualized support, and data-driven insights. Utilizing an experimental design, the study involved 150 EFL learners divided into control and experimental groups. The experimental group engaged with technology-enhanced formative assessment tools, while the control group followed traditional assessment methods. Quantitative analysis revealed a statistically significant improvement in the performance of learners exposed to the technological intervention. These findings demonstrate the potential of technology to foster more effective and dynamic formative assessment practices in EFL contexts. The study not only supports the validity of technology-integrated assessment through empirical evidence but also emphasizes its practical value in enhancing learner outcomes. The implications highlight the importance of integrating digital tools into language classrooms to meet contemporary pedagogical needs.